(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
The present study analyzes the interregional disparities in the quality of primary education in rural India. The study is based on the Annual Status of Education Report, 2010 prepared by Pratham. Quality of Education Index (QEI) has been constructed using three indices: (i) Quality of Teaching Index, (ii) School Infrastructure Index and (iii) Learning Achievement Index. It has been observed that Kerala is the only state which scores the highest in all the three indices whereas states like Bihar, Uttar Pradesh, Assam, Odisha, Jharkhand and majority of North Eastern state are at the bottom. At the regional level a high quality knowledge base on education system reform needs to be developed.